2013
DOI: 10.1134/s0018143913020021
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of phenol and its decomposition products in the electrolyte cathode of direct-current atmospheric-pressure discharge

Abstract: The application of high energy chemistry methods to water treatment for the removal of organic com pounds has been intensively studied in recent years. These methods include the treatment of solutions with gas discharge generated ozone (O 3 ), O 3 together with ultraviolet irradiation (O 3 /UV), hydrogen peroxide (H 2 O 2 ) in combination with UV, and H 2 O 2 /UV [1]. Different types of atmospheric pressure gas discharges in oxygen and air and over solutions generate all of the above factors and also cause the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There are some fragmentary data on separate products, but the detailed studies of product kinetics are not available. Recent studies have reported the effective rate constants of phenol decomposition for DC discharge in air and also revealed that the phenol decomposition results in the formation of aldehydes and carboxylic acids [13,14]. Our calculation of product balance, however, expects that other compounds have to be formed as well.…”
Section: Introductionmentioning
confidence: 81%
“…There are some fragmentary data on separate products, but the detailed studies of product kinetics are not available. Recent studies have reported the effective rate constants of phenol decomposition for DC discharge in air and also revealed that the phenol decomposition results in the formation of aldehydes and carboxylic acids [13,14]. Our calculation of product balance, however, expects that other compounds have to be formed as well.…”
Section: Introductionmentioning
confidence: 81%